Retrospect and prospect of Nicotiana tabacum genome sequencing - Tong, Zhijun; Huang, Yujie; Zhu, Qian-Hao; Fan, Longjiang; Xiao, Bingguang; Shen, Enhui (Frontiers in Plant Science, 2024)
Investigating plant genomes offers crucial foundational resources for exploring various aspects of plant biology and applications, such as functional genomics and breeding practices. With the development in sequencing and assembly technology, several Nicotiana tabacum genomes have been published. In this paper, we reviewed the progress on N. tabacum genome assembly and quality, from the initial draft genomes to the recent high-quality chromosome-level assemblies. The application of long-read sequencing, optical mapping, and Hi-C technologies has significantly improved the contiguity and completeness of N. tabacum genome assemblies, with the latest assemblies having a contig N50 size over 50 Mb. Despite these advancements, further improvements are still required and possible, particularly on the development of pangenome and telomere-to-telomere (T2T) genomes. These new genomes will capture the genomic diversity and variations among different N. tabacum cultivars and species, and provide a comprehensive view of the N. tabacum genome structure and gene content, so to deepen our understanding of the N. tabacum genome and facilitate precise breeding and functional genomics.